A review on issues and approaches for microgrid protection. (January 2017) - Brearley, Belwin J.; Prabu, R. Raja
Abstract: In a traditional power grid, power generation is done at various potential locations and transmitted into power grid and then distributed to the customer premises. The traditional grid incurs heavy investment, limited reliability, increased emissions of green house gases and increased transmission line losses. It has made the utility to opt for connecting numerous renewable based micro sources near the customer premises, as per their requirement and providing intelligent control for the grid. As a comprehensive solution, microgrids are suggested by the researchers which would provide reliable, quality and efficient supply to its customers. The connection of microgrid in the existing distribution network makes the radial network more complicated. It also causes the magnitude of fault current to change dynamically depending on the modes of operation (grid connected or islanded mode), type of distributed generator, status of distributed generators and number of distributed generators. The conventional protection schemes are designed for radial power flow with centralized power generation, which makes the existing protection scheme to fail with the microgrid. Hence, an attempt is made to relook into the basic concepts and significance of microgrid, issues faced by the microgrid in the context of protection and various protection strategies.